La sociedad fallida - Herrera León, Bernardino (Cambio Universitario, 2018)
The concept of failed State is described, from the perspective of the Center for Studies for the Peace Fund and the proposal that this institution, to turn it into an international legal element that is applied in cases of collapse of nations. In Venezuela there are the categories that describe a failed State with the internal consequences suffered by the Venezuelan population and the generation of a Venezuelan diaspora, that especially affects neighboring countries. While the Chavista regime tries to hide this reality with its powerful propaganda device. Faced with this concept, is proposed the concept of failed Society. Se describe el concepto de Estado fallido, desde la perspectiva del Centro de Estudios Fondo para la Paz y la propuesta de esta institución de convertirlo en un elemento jurídico internacional que se aplique en casos de colapso de las naciones. En Venezuela se dan las categorías que describen a un Estado fallido con las consecuencias al interno que sufre la población venezolana y la generación de una diáspora venezolana que afecta especialmente a países vecinos. Mientras el régimen chavista trata de ocultar esta realidad con su poderoso aparato propagandístico. Frente a este concepto se propone el concepto de Sociedad fallida.